Genotyping of the rs1800440 Polymorphism in CYP1B1 Gene and the rs9258883 Polymorphism in HLA-B Gene in a Spanish Cohort of 223 Patients with Frontal Fibrosing Alopecia - David Saceda-Corralo; Daniel Ortega-Quijano; Gloria Muñoz-Martín; Óscar M. Moreno-Arrones; Cristina Pindado-Ortega; Tuntas Rayinda; Ana Melián-Olivera; Carlos Azcárraga-Llobet; Patricia Burgos-Blasco; María Elena Castañeda-Bermúdez; Francisco J. del Castillo; Sergio Vañó-Galván (Medical Journals Sweden, 2023)
The pathogenesis of frontal fibrosing alopecia has been linked to specific genetic variants. CYP1B1 codes for a component of the cytochrome p450 machinery that is involved in the metabolism of xenobiotic oestrogens. The study of the prevalence of polymorphisms in this gene may help to understand their role in the development of frontal fibrosing alopecia. The aim of this study is to describe the frequency of genetic variations in the alleles HLA-B*07:02 and CYP1B1 in patients with frontal fibrosing alopecia. A cross-sectional study was designed to evaluate blood samples from patients with frontal fibrosing alopecia who attended the Dermatology Department at University Hospital Ramón y Cajal (Madrid, Spain), in search of the polymorphisms rs9258883 and rs1800440 in the alleles HLA-B*07:02 and CYP1B1, respectively. A total of 223 patients were included in the study. Among the 83.8% of patients who carried the rs9258883 polymorphism in HLA-B*07:02, 58.7% were heterozygous for this variant and it was not present in 14.8% of the cases. The majority of patients with frontal fibrosing alopecia lacked the protective rs1800440 polymorphism in CYP1B1 (75.2%). This suggests a relevant role of this variant in development of frontal fibrosing alopecia. The genetic approach to this condition might influence patient prognosis and therapy options.